The Website of Roger Wolfe as Multi-discourse Device. Literature and Persuasive Strategy (Castilla. Estudios de Literatura, 2012)
This article analyzes the website of the English-born writer Roger Wolfe as a multiple (literary, critical, essayistic and journalistic) and persuasive (ideological and promotional) discourse. The investigation aims to reveal the design and function of the persuasive strategy that structures the web and flows under a complex multi-discursive and multimedia mesh whose last intention is to persuade the site visitor about the utility to read the author. For that purpose it is always demonstrate his quality, peculiarity, independence, honesty and coherence.